'Forgiveness is a present to yourself as well': An intrapersonal model of forgiveness in victims of violent crime. (September 2013) - Field, Courtney; Zander, Jaimie; Hall, Guy
Existing models of forgiveness do not easily accommodate victims of crime. Therefore, this article presents an examination of the meaning of forgiveness from the perspective of crime victims. A grounded theory approach was adopted to analyse the data from a series of semi-structured interviews carried out with victims of serious violent offences. Results indicated that victims generally thought forgiveness was both positive and beneficial. Whereas major models of forgiveness emphasize the interpersonal nature of forgiveness, victims of crime conceived of the construct as strongly intrapersonal. Forgiveness was comprised of four parts: self-awareness, letting go, perspective-taking and moving on. Each of these aspects was examined in light of the data and contrasted with existing literature. This study establishes a new area of forgiveness research and provides further insight into the psychological experience of victims of crime.